Seashell structure under binder influence - Kamarudin, Kamarul Azhar; Mohamed, Mohamed Nasrul Hatta; Anpalagan, Ranjhini; Ismail, Al Emran; Ab Baba, Noor Wahida; Mohd Noor, Mohd Khir; Abdullah, Ahmad Sufian (Penerbit Akademia Baru, 2018)
Since the very beginning, evolution on protective materials keep going on where the material utilized as a part of plate armour continue changing, from steel, Kevlar, ceramic and the materials that can give better impact and benefit to the user. A study has been led to distinguish either seashell can be one of the fundamental source to produce protective material due to its properties calcium chloride. Seashell is crushed and chipped using variable speed rotor mill and is compressed into specimen shape. A batch of samples is tested made from seashells that mix with three different binder i.e. water, kaolin and polyethylene glycol (PEG). One batch of samples is dried at room temperature which another batch of samples are sintered at elevated controlled temperature before testing to determine their mechanical properties results. Result shows that at high temperature, specimen with water and PEG gives the highest value of Young’s modulus and ultimate strength compared to sample without temperature effect. However, temperature effect shows no differences on kaolin samples compared to room temperature curing samples